The Middle Ages in 50 objects - Gertsman, Elina (Cambridge University Press, 2018)
The array of images included in this volume reveals the full and rich history of the Middle Ages. Exploring material objects from the European, Byzantine and Islamic worlds, the book casts a new light on the cultures that formed them, each culture illuminated by its treasures. The objects are divided among four topics: the holy and the faithful; the sinful and the spectral; daily life and its fictions, and death and its aftermath. Each section is organized chronologically, and every object is accompanied by a penetrating essay that focuses on its visual and cultural significance within the wider context in which the object was made and used. Spot maps add yet another way to visualize and consider the significance of the objects and the history that they reveal.